1985
DOI: 10.3109/17453678508993038
|View full text |Cite
|
Sign up to set email alerts
|

Interface stresses in the resurfaced hip: Finite element analysis of load transmission in the femoral head

Abstract: The load transmission and interface stresses in the Wagner resurfaced femoral head were evaluated for the purpose of studying possible failure mechanisms. We found that unnatural stress patterns occur in the head and at the implant-bone interfaces, in addition to regions of stress protection in the bone, possibly enhancing interface failure and bone remodelling. However, these stresses are not higher than those reported for other kinds of prostheses, e.g. acetabular cup, tibial plateau. From these findings, to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
30
0

Year Published

1989
1989
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(35 citation statements)
references
References 8 publications
(8 reference statements)
4
30
0
Order By: Relevance
“…Despite this, resurfacing implants alter load transfer through the proximal femur; with strain being reduced in the femoral head and increased in the femoral neck (Huiskes et al, 1985;Watanabe et al, 2000;Ong et al, 2006;Cristofolini et al, 2009). The major observed complication with recent designs is neck fracture, accounting for over 40% of revisions in the Australian Orthopaedic Association National Joint Replacement Registry (2008) with an incidence of approximately 2% (Shimmin and Back, 2005).…”
Section: Introductionmentioning
confidence: 95%
“…Despite this, resurfacing implants alter load transfer through the proximal femur; with strain being reduced in the femoral head and increased in the femoral neck (Huiskes et al, 1985;Watanabe et al, 2000;Ong et al, 2006;Cristofolini et al, 2009). The major observed complication with recent designs is neck fracture, accounting for over 40% of revisions in the Australian Orthopaedic Association National Joint Replacement Registry (2008) with an incidence of approximately 2% (Shimmin and Back, 2005).…”
Section: Introductionmentioning
confidence: 95%
“…Cook et al [11] compared the load transfer in the TARA prosthesis to that in four other resurfacing prostheses, using finite element method. He noted substantial differences in the stress patterns when a TARA prosthesis was placed, This is, of course, important, because the stress concentrations are though to be responsible for loosening [24,25,32,34].…”
Section: Discussionmentioning
confidence: 99%
“…Although the precise causes of the failures have not been demonstrated beyond doubt, a number of hypotheses have been suggested, such as excessive wear particles causing osteolysis of the interfaces, the difficulty of the surgery, inviting errors, the thin polyethylene cup, disturbances of the vascularity under the metal head, and biomechanical causes related to load transfer, stress shielding and interface failure. Biomechanical finite eleCorrespondence to: M. C. deWaalMalefijt, MD, PhD ment analyses of the Tharies prosthesis [32], the ICLH prosthesis [31], the Wagner prosthesis [24,25] and the Gerard prosthesis [39] have been published. In all cases, it was found that the relatively rigid metal resurfacing cup produces unnatural stress-shielding effects in the underlying bone and stress concentrations in the bone around the cup rim.…”
mentioning
confidence: 99%
“…This was despite the effort made to downsize the femoral head that resulted in femoral neck notching in some cases. Placing the femoral component in valgus reduces the stresses in the superior aspect of the femoral head and neck [23,27,45]. Femoral components placed in 5°valgus have a factor of 6.1 reduction in the relative risk of an adverse outcome [7].…”
Section: Discussionmentioning
confidence: 99%